Physical Activity versus Sclerostin and Interleukin 6 Concentration in Patients Receiving Renal Replacement Therapy by Hemodialysis - Turoń-Skrzypińska A; Dutkiewicz G; Marchelek-Myśliwiec M; Rył A; Dziedziejko V; Safranow K; Ciechanowski K; Rotter I (Dove Medical Press, 2020)
Agnieszka Turoń-Skrzypińska,1,* Grażyna Dutkiewicz,2,* Małgorzata Marchelek-Myśliwiec,2 Aleksandra Rył,1 Violetta Dziedziejko,3 Krzysztof Safranow,3 Kazimierz Ciechanowski,2 Iwona Rotter1 1Department of Medical Rehabilitation and Clinical Rehabilitation, Pomeranian Medical University, Szczecin 71-210, Poland; 2Department of Nephrology, Transplantology and Internal Medicine, Pomeranian Medical University, Szczecin 70-111, Poland; 3Department of Biochemistry and Medical Chemistry, Pomeranian Medical University, Szczecin 70-111, Poland*These authors contributed equally to this workCorrespondence: Agnieszka Turoń-Skrzypińska Email agi.skrzypinska@gmail.comIntroduction: Chronic kidney disease and renal replacement therapy are associated with reduced motor activity, which may result in the presence of mineral bone disorders and an increase in inflammation markers. The aim of the study was to assess the relationship between the performance of daily physical activity, expressed in the number of steps performed by patients undergoing hemodialysis and the concentration of selected biochemical parameters (SCL, IL-6).Patients and Methods: The study group (B) involved 33 patients aged 59.8 ± 9.8 years from the dialysis station at the Department of Nephrology, Transplantology and Internal Medicine PUM. In group B, interventions considering an increase in physical activity expressed in the number of steps were introduced. Group C consisted of 30 people aged 54.9 (9.37), with GFR over 60 mL/min/1.73m. Physical activity was measured with pedometers. Anthropometric and biochemical parameters were assessed at baseline, after the third and sixth month of the study. Descriptive statistics, intergroup comparisons using Mann–Whitney U test and Spearman correlation analysis were performed. The level of significance was set at p≤ 0.005.Results: A relationship between IL-6 concentration and the number of steps in group B after three months of intervention was demonstrated. In group C, the concentration of SCL and IL-6 decreased with the increase in the number of steps taken. Only in group C the waist circumference decreased with the increase of the number of steps performed.Conclusion: Patients receiving renal replacement therapy by hemodialysis showed significantly lower physical activity compared to people without kidney disease. Performing bigger number of steps can lower interleukin 6 levels in hemodialysis patients.Keywords: physical activity, hemodialysis, sclerostin, interleukin 6